(untitled) (Global Journals of Research in Engineering, 2022)
The goal of this work is to present an innovative design for a smart robotic gripper which is able to grasp different randomly deployed prismatic and cylindrical packages and orient them through a mechanically passive alignment system with sensing capability It consists in a new concept of end-effector combined with an ad-hoc path planning for aligning residual worst cases The system uses gravity and an angular sensor embedded into the gripper to detect the object orientation and if necessary formulate a control strategy to align it before the release phase An initial screening experiment was executed to find the parameters that most influence the alignment angle and execution time Two worst-case pack ages were tested in different working conditions The results show that the percentage of success of the system is high even in the worst operating conditions